RAILWAY TRAFFIC OPTIMIZATION - Dušan Kamenický (Acta Polytechnica CTU Proceedings, 2017)
The article focuses on analysis of possibilities of operatic control of railway traffic and its automatization and its support by information systems. Conditions, necessary pieces of input information like infrastructure description are discussed. RailML format is mentioned as suitable format for description in railway area. Optimization criterion and use of evolutionary techniques are suggested. The system is modeled in Railway Laboratory of the Faculty of Transportation Sciences, CTU in Prague.